2012
DOI: 10.1159/000336238
|View full text |Cite
|
Sign up to set email alerts
|

Middle Lobe Syndrome: A Review of Clinicopathological Features, Diagnosis and Treatment

Abstract: Middle lobe syndrome (MLS) is a rare but important clinical entity that has been poorly defined in the literature. It is characterized by recurrent or chronic collapse of the middle lobe of the right lung but can also involve the lingula of the left lung. Pathophysiologically, there are two forms of MLS, namely obstructive and nonobstructive. Obstructive MLS is usually caused by endobronchial lesions or extrinsic compression of the middle lobe bronchus such as from hilar lymphadenopathy or tumors of neoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 76 publications
3
59
0
5
Order By: Relevance
“…The clinical symptoms that our patients had were cough, sputum, hemoptysis, chest pain and history of treatment for recurrent pneumonia, a similar finding to most other studies. 6,7,8) We found that our patients were younger than cases in Kwon 9) study (with the mean age of 47 years) and Einarsson's 7) cases (mean age of 55.7 years), but older than patients of Meteroglu 10) study with the mean age of 12.3 years.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…The clinical symptoms that our patients had were cough, sputum, hemoptysis, chest pain and history of treatment for recurrent pneumonia, a similar finding to most other studies. 6,7,8) We found that our patients were younger than cases in Kwon 9) study (with the mean age of 47 years) and Einarsson's 7) cases (mean age of 55.7 years), but older than patients of Meteroglu 10) study with the mean age of 12.3 years.…”
Section: Discussionmentioning
confidence: 43%
“…8) Plain chest radiographies may show broncho stenosis, right middle lobe collapse, inflammatory changes, and bronchiectasis. The radiographic findings most often seen in our study were atelectasis, collapse, and bronchiectasis which the last one were more than the rate of previous studies, and our broncho stenosis cases were less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The bronchi in the middle lobe have small diameters and lack collateral ventilation making clearance of secretions difficult without expectoration. [37][38][39] This idea is supported by a case series which showed that voluntary cough suppression could lead to cylindrical bronchiectasis. 40 However, evidence for cough suppression prior to developing LWS is limited to case reports.…”
Section: Pathogenesismentioning
confidence: 96%
“…Diagnosis and treatment of endobronchial obstructions can be challenging depending on the etiology. These obstructions can be diagnosed best by flexible bronchoscopy (FB) in order to directly view the pathology and, when indicated, perform a biopsy [12,13]. …”
Section: Introductionmentioning
confidence: 99%